Thermally Driven Phase Transformation and Structural Evolution of Hydrothermally Synthesized MoS2 - Saukani, Muhammad; Asmara, Yuli Panca; Kadarwati, Lutvi Vitria; Husain, Sadang (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2026)
Molybdenum disulfide (MoS2) is a transition-metal dichalcogenide with tunable physicochemical properties, making it highly suitable for applications in energy conversion, electronics, and environmental remediation. This study investigates the thermally driven phase transformation and structural evolution of MoS2 synthesized via the hydrothermal method. The aim is to explore the phase transition as a function of annealing temperature. XRD and Raman spectroscopy were used to monitor the crystal and phase changes, while SEM and TEM were used to analyze the material morphology. The results showed that the synthesized MoS2 predominantly exhibited the 1T phase, as evidenced by the characteristic Raman peaks. After annealing at 300°C, a complete transformation to the 2H phase occurred, with increased crystallinity and a well-defined trigonal prismatic structure. SEM and TEM analyses revealed that the phase transformation did not significantly alter the material morphology, which retained its flower-like structure. These findings emphasize the importance of controlling phase transformations to optimize material properties, contributing to a broader understanding of MoS2 in various technological fields.